2014
DOI: 10.1039/c4ja00256c
|View full text |Cite
|
Sign up to set email alerts
|

An alternative method for chronometric determinations involving curium

Abstract: A method for quantifying ratios of isotopes of plutonium (Pu), americium (Am), and curium (Cm) using inductively coupled plasma mass spectrometry (ICP-MS) is described that does not require radiochemical separations or a chemical yield monitor. This approach provides more rapid analysis, which is important for chronometric applications related to nuclear forensics analysis. To demonstrate its utility, we used it to quantify the ingrowth 240 Pu (t 1/2 ¼ 6563 years) from 244 Cm (t 1/2 ¼ 18.10 years) in a solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To date, there are no reported applications of ICP-MS for Cm or Cf measurement in nuclear wastes. Kurosaki et al (2014) reported the measurement of 243 Cm, 244 Cm, 245 Cm, 246 Cm and 240 Pu using a Thermo Finigan Element 2 for nuclear forensics applications. 310 Gourgiotis et al (2010) used ICP-QMS (Thermo Electron X-series) for Cm and Cf isotope measurement in transmutation studies.…”
Section: Curium/californiummentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are no reported applications of ICP-MS for Cm or Cf measurement in nuclear wastes. Kurosaki et al (2014) reported the measurement of 243 Cm, 244 Cm, 245 Cm, 246 Cm and 240 Pu using a Thermo Finigan Element 2 for nuclear forensics applications. 310 Gourgiotis et al (2010) used ICP-QMS (Thermo Electron X-series) for Cm and Cf isotope measurement in transmutation studies.…”
Section: Curium/californiummentioning
confidence: 99%
“…Kurosaki et al (2014) reported the measurement of 243 Cm, 244 Cm, 245 Cm, 246 Cm and 240 Pu using a Thermo Finigan Element 2 for nuclear forensics applications. 310 Gourgiotis et al (2010) used ICP-QMS (Thermo Electron X-series) for Cm and Cf isotope measurement in transmutation studies. 311 Sample introduction was via a quartz Peltier-cooled impact bead spray chamber (natural aspiration) and micro concentric nebulizer.…”
Section: Curium/californiummentioning
confidence: 99%
“…A different method of chronometric determinations was developed by Kurosaki et al 149 who quantied Am, Cm and Pu using a sector eld ICP-MS instrument. In particular, the isotope ratio of 240 Pu and 244 Cm was determined.…”
Section: Inorganic Chemical Catalysts and Acidsmentioning
confidence: 99%